1994
DOI: 10.1007/bf00192448
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous recanalization of recent renal artery occlusions: Report of 10 cases

Abstract: Percutaneous recanalization should be proposed in cases of renal artery occlusion, especially to avoid terminal vascular azotemia and dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…Some studies found better results in patients with oliguria [18] or with solitary or bilateral stenosis [12,19,20,21]. Recent occlusion of a renal artery also seems to be associated with a good prognosis after technically successful PTRA [22]. We believe that these results support ours since they were obtained in patients whose presentation was largely similar to that in our group B.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies found better results in patients with oliguria [18] or with solitary or bilateral stenosis [12,19,20,21]. Recent occlusion of a renal artery also seems to be associated with a good prognosis after technically successful PTRA [22]. We believe that these results support ours since they were obtained in patients whose presentation was largely similar to that in our group B.…”
Section: Discussionsupporting
confidence: 90%
“…In one of the larger series reviewing 10 patients, Boyer at al found a significant and durable improvement in serum creatinine in the six technically successful percutaneous cases. 11 As already noted, only one similar case of vascular stent placement for SRAD has been reported in the literature. 9 That patient was a 48-year-old healthy man who did have both kidneys present.…”
Section: Discussionmentioning
confidence: 95%
“…Thrombolitic treatment is recommended to start within first 6 hours of the pain. In new treatment modalities, there are spesific treatment approaches like low dose of intraarterial streptokinase injection and percutane transluminale angioplasty [17,18]. If there is a delay on diagnosis and if thrombolitic/anticoagulant therapy is not started on time, there will be surgical options leading to nephrectomy [19].…”
Section: Discussionmentioning
confidence: 99%